Analisis Metafora Pada Idiom Bahasa Jepang Yang Berunsur Mushi ‘Serangga’ - Rizki Maghfiroh Fitriana; Sri Wahyu Istana Trahutami (Diponegoro University, 2019)
(Title: Metaphorical Analysis of Japanese Idioms Containing Insect Elements) This research Metaphor analysis for Japanese idiom formed from the word insect. This research aims to describe the lexical and idiomatical meaning in Japanese idiom formed from the word insect and explains the metaphor contained in these idioms. The data in this research is taken from the Reikai Kanyouku Jiten idiom dictionary, 101 Japanese idioms, and website www.weblio.jp. The data is collected using the referring method with competent involvement and note-taking technique. Furthermore, the extralingual equivalent method is used to analyze the structure and type of metaphor. While the informal method is used to present the results of data analysis. Based on the data analysis, it was concluded that overall Japanese idioms that use the word insect have a negative meaning. In addition, most idioms show that insects are very influential animals in the lives of Japanese people.